The white queen / Philippa Gregory. - Gregory, Philippa. (Gregory, Philippa. Cousins' war, 2009)
In this account of the wars of the Plantagenets, a woman of extraordinary beauty and ambition, Elizabeth Woodville, catches the eye of the newly crowned boy king, marries him in secret and ascends to royalty. While Elizabeth rises to the demands of her exalted position and fights for the success of her family, her two sons become central figures in a mystery that has confounded historians for centuries: the missing princes in the Tower of London whose fate is still unknown.